Anthropogenic VOCs Emission Inventory and Characteristics in Jiaozuo City - Feng, Shaoxin; Feng, Shaoxin; Yue, Junhui; Sun, Linghe (International Journal of Natural Resources and Environmental Studies, 2025)
To accurately understand the atmospheric VOCs emissions in Jiaozuo City and strengthen air pollution control, this study established a 2019 anthropogenic atmospheric VOCs emission inventory using a combined "top-down" and "bottom-up" methodology. The results show that the total VOCs emissions reached 22,574 tons, with solvent use sources (40.9%), industrial process sources (25.9%), and mobile sources (18.3%) constituting the major contributors. Specifically, surface coating operations, petrochemical and chemical industries, and passenger vehicles emerged as the primary contributors to solvent use sources, industrial process sources, and mobile sources respectively. Spatially, Mengzhou City and Wuzhi County demonstrated relatively higher emissions, accounting for approximately 16% and 15% of the city’s total emissions respectively.